Use of pea agar with Tween 80 for Dalmau technique for identification of Candida albicans - Gupta, Gyan Prakash; Bhattacharyya, Sayan; Sarfraz, Asim; Sengupta, Abhishek; Singh, Shweta; Kumar, Dhirendra; Anjum, Nahid; Kumar, Ankur; -, Priyadarshini (Eastern Journal of Medical Sciences, 2017)
Introduction: Candida albicans produces devastating infections with considerable attributable mortality. Identification rests of Dalmau technique using rice extract agar, which is very prone to aerial contamination and drying and breakage. Materials and Methods: We here evaluated pea agar, with and without Tween 80, as medium for Dalmau technique for identifying C. albicans and compared it with rice extract agar. Results: Pea agar with Tween 80 was a very useful medium for identifying C. albicans. Conclusion: Pea agar with Tween 80 can be used for Dalmau technique for C. albicans identification.